2012
DOI: 10.1515/ijamh.2012.047
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of cervical cancer screening among Greek students: a short report

Abstract: Cervical cancer is a major cause of death in the developing world. The Papanicolaou (Pap) smear is a screening test that detects abnormal cells before they advance to cancer. The objective of this study was to assess the knowledge, attitude, and practice of cervical cancer screening among Greek students. A sample of 472 female students participated in the present study. Interviews were performed using a structured questionnaire. Of the participants, 94.07% were aware of the Pap test and 67.34% reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Similar studies conducted in Malaysia [14], South Africa [15], Kolkata [16] and in the United States of America [17,18] reported comparable results. About 53% (n = 353) of the participants were aware of the purpose of Pap test which is much lower than those reported from studies conducted among Taiwanese (80%) [19] and Greek (94%) [20] students. Only about 25% of our study respondents knew about the link between smoking and cervical cancer which is slightly higher than studies reported from Sri Lanka (20.8%) [21], Nepal (0.2%) [21] and Ghana (1%) [22] but much lower than that reported from studies conducted in Malaysia (61%) [23].…”
Section: Discussionmentioning
confidence: 63%
“…Similar studies conducted in Malaysia [14], South Africa [15], Kolkata [16] and in the United States of America [17,18] reported comparable results. About 53% (n = 353) of the participants were aware of the purpose of Pap test which is much lower than those reported from studies conducted among Taiwanese (80%) [19] and Greek (94%) [20] students. Only about 25% of our study respondents knew about the link between smoking and cervical cancer which is slightly higher than studies reported from Sri Lanka (20.8%) [21], Nepal (0.2%) [21] and Ghana (1%) [22] but much lower than that reported from studies conducted in Malaysia (61%) [23].…”
Section: Discussionmentioning
confidence: 63%
“…While studies among female university students in high income countries found a higher participation rate in screening for cervical cancer, e.g. 44.8% in Greece (Bakogianni et al, 2012) and 41% in USA (Durvasula et al, 2006).…”
Section: Attitudes and Practice Of Cervical Cancer Screening Among Fementioning
confidence: 99%
“…The range of awareness in various studies was 53% in Bhutan, 80% in Taiwan, and 94% in Greece. 6,16,17 Knowledge regarding vaccination and treatment is dismal too with only 30% of study population having some awareness. This has been seen in other studies among both Indian 18 and international graduates too.…”
Section: Discussionmentioning
confidence: 99%